ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2021 - Andri; Muhammad Kadafi; Juwita Aprillia (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
The purpose of this study was to identify and analyze the factors that influence stock underpricing. This research method is descriptive statistical analysis, classical assumption test, regression test, and hypothesis testing. Data is processed with SPSS (Statistical Package for Social Science). The results of this study indicate that partially underwriter reputation and financial leverage have a significant effect on underpricing while auditor reputation, company age, company size, Earning per share (EPS), Return on assets (ROA) have no significant effect on underpricing in companies at the time of Public Offering Premiere on the Indonesia Stock Exchange.